ISLAMIC LEGAL AND MYSTICAL THOUGHT IN THE AGE OF ARTIFICIAL INTELLIGENCE:BETWEEN DATA,DEEN,AND DIGNITY (Contemporary Journal of Social Science Review, 2025)
This article explores the intersection of Islamic legal and mystical thought with the emerging realities of Artificial Intelligence (AI), situating the discourse within the broader tension between data, dīn (religion), and human dignity. Drawing on classical sources of Islamic jurisprudence Qur’an, Sunnah, ijmāʿ, and qiyās as well as the juristic traditions of fiqh al-muʿāmalāt and fiqh al-nawāzil, the study examines how Shariah principles can provide ethical frameworks for AI development, deployment, and governance. At the same time, it engages with the mystical dimensions of Islam, especially the concepts of insān al-kāmil (the Perfect Human), rūḥ (soul), ʿaql (intellect), and ihsān (spiritual excellence), in order to highlight the spiritual anthropology that resists the reduction of human beings to mere data points.The analysis proceeds in two parallel trajectories: the legal trajectory, which emphasizes justice, maṣlaḥa (public interest), and maqāṣid al-sharīʿa (higher objectives of law) as guiding principles in evaluating AI applications in finance, medicine, and governance; and the mystical trajectory, which underscores the primacy of human dignity, the sanctity of the soul, and the ethical imperative of ihsān in an age increasingly dominated by surveillance, automation, and algorithmic control. By bringing these two trajectories into dialogue, the article argues for an integrated Islamic framework of AI ethics that is both normatively grounded in revelation and spiritually enriched by Sufi insights.Ultimately, the study contends that the future of AI in Muslim societies must neither be technophobic nor uncritically adopt secular paradigms. Instead, it must embody the Qur’anic call to balance—a middle path that safeguards faith, preserves human autonomy, and affirms dignity in the face of technological determinism.